Description and Correlation of Blood Pressure Measures to Health Behaviors among Uninsured Individuals Receiving Physical Therapy Services at a Student-Run Clinic - Sara Arena; Martha Schiller; Dalia Mhaid; Hussain Al-Qattan; Jill Pysh (Journal of Student-Run Clinics, 2018)
Background: The purpose of this observational study is 1) to describe the prevalence of pre-hypertension (P-HTN) and hypertension (HTN) blood pressure (BP) measures and associated self-reported health behaviors among uninsured women at a student-run clinic (SRC) for physical therapy and 2) to analyze correlations between BP measures and the self-reported health behaviors of this population. Self-reported health behaviors included physical activity, fruit and vegetable consumption, weight management, and smoking behaviors.Methods: Demographic information, BP measurements, and behavioral assessments were collected on patients referred to the Wayne State University-Super All Year Detroit Physical Therapy Clinic between May 2014 and April 2015.Results: Thirty-six females (34 African-American) with a mean age of 52 (SD=9.0) years were included. Pre-hypertension and HTN BPs were identified in 55.6% and 19.4% of the women, respectively. Among women with no prior HTN diagnosis, the prevalence of P-HTN and HTN BPs was 40.0% and 10.0%, whereas the prevalence of P-HTN and HTN BPs was 61.5% and 23.1% in women with a prior HTN diagnosis. Among study participants, 50% engaged in recommended physical activity levels, 50% consumed at least five fruits and vegetable servings per day, 27.8% maintained a healthy weight, and 64.7% abstained from smoking. A significant Spearman’s rank correlation was identified between a higher frequency of reported positive health behaviors and a lower systolic BP (r=-0.369, p=0.027).Conclusions: Identification of elevated BPs or reduced adherence to recommended healthy behaviors may guide physical therapists or other health care providers to choose health-promoting interventions that enhance patients’ health and wellness.